Linear Growth Deficit Continues to Accumulate beyond the First 1000 Days in Low- and Middle-Income Countries: Global Evidence from 51 National Surveys. Issue 9 (18th June 2014) - Leroy, Jef L.; Ruel, Marie; Habicht, Jean-Pierre; Frongillo, Edward A.
Abstract: Growth faltering is usually assessed using height-for-age Z-scores (HAZs), which have been used for comparisons of children of different age and sex composition across populations. Because the SD (denominator) for calculating HAZ increases with age, the usefulness of HAZs to assess changes in height over time (across ages) is uncertain. We posited that population-level changes in height as populations age should be assessed using absolute height-for-age differences (HADs) and not HAZs. We used data from 51 nationwide surveys from low- and middle-income countries and graphed mean HAZs and HADs by age. We also calculated annual changes in HAZs and HADs and percentage of total height deficit accumulated annually from birth to age 60 mo using both approaches. Mean HAZ started at −0.4 Z-scores and dropped dramatically up to 24 mo, after which it stabilized and had no additional deterioration. Mean HAD started at −0.8 cm, with the most pronounced faltering occurring between 6 and 18 mo, similar to HAZ. However, in sharp contrast to HAZ, HAD curves had continued increases in the deficit of linear growth from 18 to 60 mo, with no indication of a leveling off. Globally, 70% of the absolute deficit accumulated in height (HAD) at 60 mo was found to be due to faltering during the first "1000 days" (conception to 24 mo), but 30% was due to continued increases in deficit from age 2 to 5 y. The use of HAZ masks these changes because of age-related changes in SD. Therefore, HAD, rather than HAZ, should be used to describe and compare changes in height as children age because detecting any deficit compared with expected changes in height as children grow is important and only HAD does this accurately at all ages. Our findings support the current global programmatic momentum to focus on the first 1000 d. Research is needed to better understand the dynamics and timing of linear growth faltering using indices and indicators that accurately reflect changes over ages and to identify cost-effective ways to prevent growth faltering and its consequences throughout the lifecycle.